1994
DOI: 10.1161/01.str.25.1.202
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin and intercellular adhesion molecule-1 expression after focal brain ischemia and reperfusion.

Abstract: Background and Purpose Polymorphonuclear leukocytes have been implicated in the development of the "no-reflow" phenomenon after focal cerebral ischemia and reperfusion. To further understand the role of granulocytes in microvascular occlusions, the responses of the granulocyte-endothelial cell adhesion molecules P-selectin and intercellular adhesion molecule-1 during middle cerebral artery ischemia and reperfusion were examined in a primate model.Methods Twelve adolescent male baboons were used for 2-hour midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
211
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(218 citation statements)
references
References 57 publications
4
211
0
3
Order By: Relevance
“…The animals employed for these studies overlapped with those participating in published work on endothelial receptor up-regulation (Okada et al, 1994). Animals weighing 6.3-11.7 kg were conditioned for human contact and observed to be clinically without infection during a mandated quar antine period before entry into this study.…”
Section: Methodsmentioning
confidence: 99%
“…The animals employed for these studies overlapped with those participating in published work on endothelial receptor up-regulation (Okada et al, 1994). Animals weighing 6.3-11.7 kg were conditioned for human contact and observed to be clinically without infection during a mandated quar antine period before entry into this study.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the expression of PECAM-1 or other cell adhesion molecules were increased in the spinal cord ischemia [4], focal cerebral ischemia [9,29], and other peripheral ischemia models [31,33,34]. The elevation of PECAM-1 immunoreactivity and its protein level in vessels increases the transmigration of lymphocytes and neutrophils [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, treatment with methanol resulted in an almost complete abrogation of intracellular esterase activity, resulting in loss of fluorescence upregulated on brain microvessels located within the ischaemic lesion, indicating that the selectins facilitate the adhesion of inflammatory cells and subsequently increase neuronal injury. 44,45 We hypothesised that the immunomodulatory drug MMF can influence the process of monocyte adhesion to endothelial cells, possibly by altering the glycosylation of adhesion molecules. It has been described that different adhesion molecules require glycosylation for the activation of their adhesive functions, 18 consequently, Heemann et al 46 showed that MMF treatment reduced leucocyte infiltration into transplanted kidneys.…”
Section: Discussionmentioning
confidence: 99%